The impact of environmental quality components on enhancing social health: a case study on residential complexes of Ardabil city - Negari, Maleka; Javan Majidi, Javad; Alavizadeh, Elham (Social Determinants of Health, 2025)
Background: Nowadays, in the evaluation of urban quality, urbanization is considered as one of the key factors affecting individual and social health. In this regard, just as human health is largely influenced by city programs and goals, urban life also depends on improving the overall quality of health. Therefore, attention must be paid to environmental quality and the enhancement of social health within residential complexes. Methods: This study examined the impact of environmental quality components on improving social health in residential complexes in Ardabil City, specifically in the Laleh Sabalan and Honarmandan complexes. This research employed a mixed-methods approach. In the qualitative phase, data were collected through interviews and focus group discussions, while in the quantitative phase, survey methods using both standardized and researcher-made questionnaires were utilized. Participants in the qualitative phase were selected through purposive sampling among architecture experts and academics. In the quantitative phase, stratified random sampling was used, with a sample size of 271 residents from the mentioned residential complexes. For data analysis, SPSS and LISREL software were employed, along with regression analysis, Pearson tests, and structural equation modeling. Results: The findings revealed that environmental quality components—such as economic factors, socio-human aspects, environmental dimensions, functional and physical characteristics of residential units, aesthetics, visual appeal, use of natural elements, lighting, safety, and perceptual meanings—significantly impact social health enhancement. Notably, components like the use of natural elements, economic dimension, and safety had the most substantial effects on residents’ social health. Overall, each dimension of environmental quality was found to meaningfully contribute to improved social health in residential complexes. Conclusion: Based on these findings, it can be concluded that to increase social health within residential areas, greater attention must be paid to environmental quality indicators.